Age-related changes in the cytoplasmic ultrastructure of feline oocytes - Brągiel Natalia; Perrin John; Młodawska Wiesława; Niżański Wojciech; Podhorska-Okołów Marzenna; Haczkiewicz-Leśniak Katarzyna; Kulus Michał; Ochota Małgorzata (Scientific Reports)
Abstract This study elucidates the impact of aging on the cellular architecture of feline oocytes, with a particular emphasis on organelles essential for fertilization and embryo development. Using transmission electron microscopy (TEM), the research compares oocytes from prepubescent, cycling adult, and aged cats, revealing notable differences in the arrangement of key structures, particularly mitochondria, lipid droplets, and vacuoles. Oocytes from adult donors are at their metabolic peak, demonstrating a higher concentration of mitochondria near lipid droplets, supporting efficient energy metabolism. In contrast, younger and older oocytes exhibit larger lipid droplets and reduced mitochondrial density, indicative of diminished metabolic activity. These findings not only underscore the necessity of selecting an optimal donor age for in vitro fertilization but also suggest potential biomarkers for oocyte quality assessment. This novel insight offers promising strategies to enhance reproductive success, improve assisted reproduction outcomes, and support feline conservation efforts.